Iowa's archaeological past - Alex, Lynn Marie, 1948- (Bur oak book., 2000)
Iowa has more than eighteen thousand archaeological sites, and research in the past few decades has transformed our knowledge of the state's human past. Examining the projectile points, potsherds, and patterns that make up the archaeological record, Lynn Alex describes the nature of the earliest settlements in Iowa, the development of farming cultures, the role of the environment and environmental change, geomorphology and the burial of site, interaction among native societies, tribal affiliation of early historic groups, and the arrival and impact of Euro-Americans. In a final chapter, she.